Involuntary Falls in Patients with Chronic Kidney Diseases on Nephrology Wards: Research Advances and Future Perspectives - Liao Y; Wang A; Sui W; Khan A; Xiong Z; Yang G (Dove Medical Press, 2024)
Yumei Liao,1,* Aihong Wang,1,* Wenjuan Sui,2 Abbas Khan,3 Zibo Xiong,1,4,5 Guang Yang1,4,5 1Division of Renal Medicine, Peking University Shenzhen Hospital, Peking University, Shenzhen, Guangdong, 518036, People's Republic of China; 2Institute of City Strategy Studies, Guangdong University of Foreign Studies, Guangzhou, Guangdong, 510006, People's Republic of China; 3Department of Nutrition and Health Promotion, University of Home Economics Lahore Pakistan, Lahore, 54000, Pakistan; 4Institute of Nephrology, Shenzhen Peking University-Hong Kong University of Science and Technology (PKU-HKUST) Medical Center, Shenzhen, Guangdong, 518036, People's Republic of China; 5Shenzhen Clinical Research Centre for Urology and Nephrology, Shenzhen, Guangdong, 518036, People's Republic of China*These authors contributed equally to this workCorrespondence: Zibo Xiong; Guang Yang, Email xiong0301@163.com; guang.yang@pkuszh.comBackground: Nephrology nursing faces an inevitable challenge when it comes to falls. This study aims to review existing literature on falls in chronic kidney disease (CKD) patients and to discuss potential solutions.Methods: This review explores the characteristics and causes of falls in CKD patients, elucidate the underlying mechanisms, shares better nursing practices, and discusses both current prevention strategies as well as potential future interventions.Results: CKD patients often experience consciousness impairment and motor dysfunction due to factors such as muscle atrophy, nerve damage, malnutrition, anemia, fluid-electrolyte imbalances, hormonal disorders, and dialysis. Additionally, this study not only shares insights from nursing experience with these patients, but also reviews current evidence-based fall prevention strategies and proposes potential new interventions that could be tested in future research.Conclusion: CKD may increase the risk of involuntary falls in patients due to consciousness impairment and motor dysfunction. Advocating for a standardized expert consensus on fall risk assessment and comprehensive care for CKD patients would enhance the nursing framework in nephrology wards and help patients decrease their fall risk and elevate their quality of life.Keywords: falls, chronic kidney diseases, dialysis, nephrology nursing, anemia